Effect of verapamil and sodium cromoglycate on leukotriene D4 induced bronchoconstriction in patients with asthma. - Roberts, J A (1986)
Leukotriene D4 (LTD4) may be an important mediator in asthma. The effect of verapamil and sodium cromoglycate on LTD4 induced bronchoconstriction has been examined in seven patients with asthma. The bronchoconstrictor response to increasing concentrations of inhaled LTD4 (0.0032-50 micrograms/ml) was assessed by measuring changes in FEV1, specific airways conductance, and flow rate at 30% of vital capacity (V30(p)). Results were expressed as the provocation concentration (PC) producing a 10% fall in FEV1 (PC10FEV1), a 35% fall in specific airways conductance (PC35SGaw), and a 30% fall in flow at 30% of vital capacity (PC30 V30(p)). Neither verapamil nor cromoglycate inhibited LTD4 induced bronchoconstriction in asthmatic subjects. These results suggest that in asthmatic patients LTD4 induced bronchoconstriction is not mediated via verapamil or cromoglycate sensitive mechanisms.